Los “escotomas” del campo médico que limitan su papel en la salud sexual y reproductiva (SSR) de los adolescentes: ideas para superarlos (2014)
ABSTRACT: This paper reviews the role of the medical field in adolescent sexual and reproductive health (ASRH). A brief historical account of the emergence of two specialties -Adolescent and Young Adult Medicine and Youth and Adolescent Gynecology- shows a predominance of the medical views and practices that act as “scotomas” limiting the role on ASRH promotion. It offers a conceptual framework built from critical social sciences, standing out the innovative contributions made by the Latin American collective health and feminism movements to overcome such “scotomas” by offering a better comprehension of key points involved in ASRH. Among them: the social and gender determination on health, the hegemonic medical institutional discourses and practices that perpetuate health inequities in relation to sexualities, subjectivities and identities of patients. The concept of “sexual citizenship” is presented as a useful analytical and methodological tool to integrate all these key points. Their incorporation into medical training programs would produce a deep turn in medicine granting the fulfillment of goals set out in the international conferences of Cairo and Beijing that urged governments to carry out actions to attend adolescent’s needs and demands by granting their sexual and reproductive rights (SRR), thus providing the enhanced role that medicine must play in ASRH.